2008
DOI: 10.1042/cs20070226
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin/PBEF/Nampt: structure, regulation and potential function of a novel adipokine

Abstract: Over the last few years, it has become obvious that obesity and insulin resistance are linked by a variety of proteins secreted by adipocytes. Visfatin/PBEF (pre-B-cell colony-enhancing factor) has recently been identified as a novel adipokine with insulin-mimetic effects. Furthermore, an enzymatic function has been reported that reveals visfatin/PBEF as Nampt (nicotinamide phosphoribosyltransferase; EC 2.4.2.12.). Moreover, reports on the structure and hormonal regulation of visfatin/PBEF/Nampt have given fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
2
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 62 publications
4
84
2
12
Order By: Relevance
“…In the past years, a rate-limiting component of the mammalian NAD biosynthesis pathway from nicotinamide called nicotinamide phosphoribosyltransferase (NAMPT) has emerged as a new adipokine [7][8][9][10]. NAMPT was first identified as pre-B cell colony-enhancing factor (PBEF), a highly conserved 52 kDa cytokine-like protein that enhances the maturation of B cell precursors in the presence of interleukin (IL)-7 and stem cell factor [11] and inhibits the apoptosis of neutrophils [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, a rate-limiting component of the mammalian NAD biosynthesis pathway from nicotinamide called nicotinamide phosphoribosyltransferase (NAMPT) has emerged as a new adipokine [7][8][9][10]. NAMPT was first identified as pre-B cell colony-enhancing factor (PBEF), a highly conserved 52 kDa cytokine-like protein that enhances the maturation of B cell precursors in the presence of interleukin (IL)-7 and stem cell factor [11] and inhibits the apoptosis of neutrophils [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, this protein turned out to be identical to PBEF [pre-Bcolony-enhancing factor] and Nampt [nicotinamide phosphoribosyltransferase]. Furthermore, the claim that visfatin was an insulin-like peptide has been withdrawn (Sommer et al, 2008) and its gene expression in human visceral fat is no higher than in subcutaneous fat (Berndt et al, 2005;. Circulating concentrations of visfatin as measured by an ELISA specific for full-length visfatin are not elevated in obesity (Retnakaran et al, 2008;Korner et al, 2007).…”
Section: Visfatin/pbef/namptmentioning
confidence: 99%
“…A positive correlation between visfatin and BMI as well as visceral fat mass has been reported . However, during the past years, contradictory results regarding waist circumference, glucose level, IR, visceral and subcutaneous adipose tissues have also been emerged in a clinical setting (Sommer et al, 2008). Berndt et al demonstrated that serum visfatin level did not correlate with visceral fat mass and that mRNA expression of the gene encoding visfatin was similar in visceral and subcutaneous adipose tissue (Berndt et al, 2005).…”
Section: Visfatinmentioning
confidence: 99%